Answer:
(b) 67
Step-by-step explanation:
A solution to the differential equation describing the temperature according to Newton's Law of Cooling could be written as ...
T = (final temp) + (initial difference)×(decay factor)^t
where the decay factor is the fraction of change during 1 unit of time period t.
__
Here, the initial difference of 100-25 = 75 degrees decays to 90-25 = 65 degrees in 1 minute. So, the units of t are minutes, the decay factor is 65/75, the initial difference is 75 degrees, and the final temperature is 25 degrees. That lets us write the equation as ...
T = 25 +75(65/75)^t
Then for t=4, the temperature is ...
T = 25 +75(13/15)^4 ≈ 67.3 . . . . degrees
After 4 minutes the temperature of the coffee is about 67 degrees.
30 of the $3 tickets were sold
70 of the $2 tickets were sold.
(3*30) + (2*70) = 230
Answer:
(A)
Length of DE = √17
EF = √18
DF = √17
(B) Slope of DE = 4
EF = 1
DF = 1/4
(C) Isosceles triangle.
Step-by-step explanation:
See attached image.
Answer:
Step-by-step explanation:
First confirm that x = 1 is one of the zeros.
f(1) = 2(1)^3 - 14(1)^2 + 38(1) - 26
f(1) = 2 - 14 + 38 - 26
f(1) = -12 + 38 = + 26
f(1) = 26 - 26
f(1) = 0
=========================
next perform a long division
x -1 || 2x^3 - 14x^2 + 38x - 26 || 2x^2 - 12x + 26
2x^3 - 2x^2
===========
-12x^2 + 28x
-12x^2 +12x
==========
26x -26
26x - 26
========
0
Now you can factor 2x^2 - 12x + 26
2(x^2 - 6x + 13)
The discriminate of the quadratic is negative. (36 - 4*1*13) = - 16
So you are going to get a complex result.
x = -(-6) +/- sqrt(-16)
=============
2
x = 3 +/- 2i
f(x) = 2*(x - 1)*(x - 3 + 2i)*(x - 3 - 2i)
The zeros are
1
3 +/- 2i
Answer:
candice
Step-by-step explanation:
candice?